Feasibility study of hybrid retrofits to an isolated off-grid diesel power plant - Rehman, S. (2020)
Abstract The green sources of energy are being encouraged to reduce the environmental pollution and combat the global warming of the planet. A target of 12% usage of wind energy only has been agreed by the UNO country members to achieve by 2020. So, the power of the wind is being used to generate electricity both as grid connected and isolated wind-diesel hybrid power plants. This paper performed a pre-feasibility of wind penetration into an existing diesel plant of a village in north eastern part of Saudi Arabia. For simulation purpose, wind speed data from a near by airport and the load data from the village have been used. The hybrid system design tool HOMER has been used to perform the feasibility study. In the present scenario, for wind speed less than 6.0 m/s the, the existing diesel power plant is the only feasible solution over the range of fuel prices used in the simulation. The wind diesel hybrid system becomes feasible at a wind speed of 6.0 m/s or more and a fuel price of 0.1 $/L or more. If the carbon tax is taken into consideration and subsidy is abolished then it is expected that the hybrid system become feasible. The maximum annual capacity shortage did not have any effect on the cost of energy which may be accounted for larger sizes of wind machines and diesel generators. It is recommended that the wind data must be collected at the village at three different heights using a wind mast of 40m for a minimum of one complete year and then the hybrid system must be re-designed. r 2006 Elsevier Ltd. All rights reserved. ARTICLE IN PRESS www.elsevier.com/locate/rser 1364-0321/$ - see front matter r 2006 Elsevier Ltd. All rights reserved. doi:10.1016/j.rser.2005.05.003 Corresponding author. Tel.: +9663 860 3802; fax: +966 3 860 3996. E-mail address: srehman@kfupm.edu.sa (S. Rehman). 1Home page: http://staff.kfupm.edu.sa/ri/srehman.